Bahasa Inklusif dalam Pendidikan Islam: Membangun Komunikasi Ramah Anak untuk Mencegah Kekerasan Verbal: indonesia - Miratul Hayati, Miratul Hayati (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
Verbal abuse against early childhood often occurs in educational settings, yet its impact frequently goes unnoticed. This study focuses on how inclusive language in Islamic education can serve as a preventive strategy against verbal abuse in early childhood education (PAUD). Using a qualitative approach through a literature review of 15 related journals and thematic analysis, this research highlights four main themes: the forms and impacts of verbal abuse, inclusive communication strategies, integration of Islamic values in language, and the role of Islamic early childhood teachers.The findings indicate that the use of inclusive language grounded in the values of rahmah (compassion), ‘adl (justice), and karamah insaniyah (human dignity) can create a safe, supportive, and child-friendly learning environment. Islamic early childhood teachers play a crucial role in applying language that educates without judgment, as part of their educational and spiritual responsibility. This study recommends strengthening teacher training and developing communication curricula based on Islamic values to prevent verbal abuse and holistically shape